IMPLEMENTATION STRATEGY OF STREET VENDORS ARRANGEMENT POLICY - Nugraha, Dhion Fasesa (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The existence of street vendors (PKL) as one of the informal sectors that is recognized as having advantages compared to other sectors but the fact that the existence of street vendors (PKL) creates new problems such as traffic chaos and loss of the beauty of the city. This research aims at the implementation strategy of Street Vendor structuring policy in the Kadipaten Market of Majalengka Regency, knowing the factors that support or hinder the implementation of local government policies towards Street Vendors in the Kadipaten Market of Majalengka Regency and efforts in the Strategy for implementing the Street Vendor stage policy in the Majalengka Regency Duchy Market. The type of research used is the type of qualitative descriptive research. The informants in this study were the main informants, namely 2 Koperindag employees, the key informants, namely 5 Street Vendors (PKL) and supporting informants, namely 2 communities. Based on the results of the research conducted, the implementation of local government policies towards Street Vendors (PKL) in the Kadipaten Market of Majalengka Regency is still not fully in accordance with Regional Regulation No. 11 of 2010 concerning the arrangement of Street Vendors (PKL) in Majalengka Regency or in other words unsuccessful implementation. This is caused by several problems such as a less strategic place, lack of funds, the adaptation of a new place that emerged that made Street Vendors (PKL) choose to sell again was in the Kadipaten Market of Majalengka Regency, a less strategic place. Efforts in the implementation strategy include human resources, non-human resources, bureaucracy and cooperation.